Evaluation of the Impacts of Design Changes on Construction Projects (Case Study: Architectural Works at the Christian Center) - Karundeng, Adriana; Dwars Soukotta; Floren Agnesia Sinaga (Jurnal Ilmiah Teknik, 2025)
This study aims to evaluate the impact of design changes on the implementation of construction projects, using the Christian Center Architecture project in Manado City as a case study. The primary focus of the research is to analyze changes from the perspectives of technical aspects, cost, time, and quality resulting from design revisions during project execution. The methods used include document review, structured and semi-structured interviews with relevant stakeholders, as well as field observations to compare plans with on-site realizations. The results indicate that the design changes were mainly caused by discrepancies between the initial planning drawings and actual site conditions, as well as the functional needs of the project owner. The impacts include an increase in the volume of technical work, adjustments to execution methods, an extension of the project duration from 210 to 250 calendar days, and an improvement in work quality without any change in contract value due to the fixed-budget system (APBD). Although some of the changes resulted in improvements in terms of function and aesthetics, overall, the design changes posed challenges in maintaining the effectiveness and efficiency of project implementation. Therefore, a systematic and well-documented design change management process is required to ensure effective project execution and the quality of the final outcome.